Exosomal long non-coding RNAs in the diagnosis and oncogenesis of pancreatic cancer. (31st March 2021) - Robless, Eunice Eugenia; Howard, Justin Andrew; Casari, Ilaria; Falasca, Marco
Abstract: Extracellular vesicles, specifically exosomes, play a significant role as an extracellular messenger through their transporting cargo. Of particular interest are the potential roles they play in pancreatic cancer, one of the leading causes of cancer-related mortality worldwide. Pancreatic Ductal Adenocarcinoma displays high chemo-resistance and metastatic ability, which may be influenced by cancer-derived exosomes carrying proteins, lipids and RNA. To date, among the most extensively examined exosomal molecular cargo there are long non-coding RNAs (lncRNAs) that, despite the increasing interest in their role and functions, are relatively poorly understood compared to other RNA transcripts. Nevertheless, we have witnessed an increasing interest for lncRNAs roles and functions in the past decade. For example, lncRNAs have been investigated as potential biomarkers for diagnosing pancreatic cancer and may have a role as therapeutics targets for precision medicine, but may also directly intervene in tumour progression features such as metastasis, epithelial to mesenchymal transition and resistance of cancer cells towards chemotherapy agents. The function of lncRNAs within various cancer exosomes is still undefined. In this review, we summarize the current knowledge on pancreatic cancer-derived exosome specific lncRNAs having prominent roles in genome integrity, pancreatic cancer progression and in other oncogenic hallmarks. Highlights: Pancreatic cancer has the lowest survival rate of all cancer types. Exosomes derived from pancreatic cancer cells carry a unique cargo, including long non-coding RNAs (lncRNAs). Exosomal lncRNAs functions contribute to pancreatic cancer progression and metastasis. Exosomal LncRNAs have emerged as potential biomarkers that may rival current biomarkers used.